2014
DOI: 10.1103/physrevb.89.081303
|View full text |Cite
|
Sign up to set email alerts
|

Experimental observation of exciton splitting and relaxation dynamics from PbS quantum dots in a glass matrix

Abstract: Multiple optical transitions from PbS quantum dots (QDs) in glass matrix are observed. Energy separations between them amount up to ∼200 meV. Instead of being due to a size distribution of QDs, they are found to be related to a splitting of the lowest exciton levels. Systematic analysis of the relaxation dynamics reveals the lifetimes of the split states ranging from sub-100-ns to ∼μs. Moreover, we observe excited and "intrinsic" states having a sub-100-ps and ∼ns lifetime, respectively. The behavior of the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Even more important, the integral intensity of the fast component depends in a superlinear way on excitation, as shown in Figure d, which shows a threshold‐like excitation value at 20 μJ · cm −2 ; and the fast component shows no dependencies of excitation, and even temperature, therefore, the fast component with a typical decay time of ∼40 ps could account for amplified spontaneous emission (ASE). This is consistent with the observation of stimulated emission in PbS:Glass material system …”
supporting
confidence: 92%
“…Even more important, the integral intensity of the fast component depends in a superlinear way on excitation, as shown in Figure d, which shows a threshold‐like excitation value at 20 μJ · cm −2 ; and the fast component shows no dependencies of excitation, and even temperature, therefore, the fast component with a typical decay time of ∼40 ps could account for amplified spontaneous emission (ASE). This is consistent with the observation of stimulated emission in PbS:Glass material system …”
supporting
confidence: 92%
“…Similar sub-band emission has been observed in lead chalcogenide QDs in a variety of chemical environments. [41][42][43][44] Chuang et al identified this state as the likely origin of the large open-circuit voltage deficit in PbS QD photovoltaics. 3 Although the trap state is lower in energy by an amount ($170 meV) many times greater than the available thermal energy at 300 K ($25 meV), the room-temperature emission spectrum is nonetheless dominated by the band edge.…”
Section: Charge-carrier Equilibrium Between Band Edge and Trap Statementioning
confidence: 99%
“…[70] Instead of being due to the size difference of QDs, dual-band emission with energy separations of 200 meV was also found to be related to a splitting of the lowest exciton levels in PbS QDsdoped borosilicate glass with a rather narrow QD size distribution. [71] Large full-width at half-maximum (FWHM) of these dual-band PL (≈600 nm) has potentials for broad-band infrared light sources. [70,71] As for QDs-doped fiber amplifier (QDFA), both theoretical simulation and experimental exploration were carried out.…”
Section: Ivb-via Group Qds-embedded Glassesmentioning
confidence: 99%
“…[71] Large full-width at half-maximum (FWHM) of these dual-band PL (≈600 nm) has potentials for broad-band infrared light sources. [70,71] As for QDs-doped fiber amplifier (QDFA), both theoretical simulation and experimental exploration were carried out. Wundke et al reported the optical gain at 1.3 µm of PbS QDs-embedded glass for the first time.…”
Section: Ivb-via Group Qds-embedded Glassesmentioning
confidence: 99%